2006
DOI: 10.1111/j.1747-0765.2006.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Drought response of dry-seeded rice to water stress timing and N-fertilizer rates and sources

Abstract: Dry seeding has been identified as an option for increasing cropping intensity and productivity in rainfed ricelands. Managing drought and nutrients are important for increasing yield, but the interactive effects of drought and nutrients on dry-seeded rice (Oryza sativa L.) growth have not been systematically investigated. Two experiments were carried out in 1994 and 1995 to analyze the effects of N fertilizer rate and the use of controlled-release fertilizers (CRFs) on the growth and yield of dry-seeded rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 11 publications
4
8
0
1
Order By: Relevance
“…Though water-related parameters to quantify the osmotic stress were not measured, we assumed that the effect of osmotic stress could adequately mimic that of drought at a similar magnitude of osmotic potentials, as concluded by previous authors (e.g., Kauffman and Eckard, 1971;Michel, 1971;Attree and Fowke, 1993). This assumption was supported by the similarity between findings in this study and those of previous authors (Wopereis et al, 1996;Tuong et al, 2002;Castillo et al, 2006). The higher N concentration in the stressed plants suggests that osmotic stress limited growth more than N uptake by the plants.…”
Section: Discussionsupporting
confidence: 92%
“…Though water-related parameters to quantify the osmotic stress were not measured, we assumed that the effect of osmotic stress could adequately mimic that of drought at a similar magnitude of osmotic potentials, as concluded by previous authors (e.g., Kauffman and Eckard, 1971;Michel, 1971;Attree and Fowke, 1993). This assumption was supported by the similarity between findings in this study and those of previous authors (Wopereis et al, 1996;Tuong et al, 2002;Castillo et al, 2006). The higher N concentration in the stressed plants suggests that osmotic stress limited growth more than N uptake by the plants.…”
Section: Discussionsupporting
confidence: 92%
“…A threshold of 40 kPa during a single stage (3L-PI, FL-PM) and at all three stages significantly reduced yield by 39-48% in comparison with the flooded control, and yields with 40 kPa were also lower than yields of all treatments with 10 kPa thresholds at one or all stages, but similar to yields with 20 kPa thresholds. Castillo et al (2006) found similar yield reductions with severe stress applied during part of the period PI-FL or part of FL-PM. In a field experiment, De Datta et al (1973b) found 30 and 40% yield reductions with a 15 kPa threshold for two varieties (IR20 and MI-48), and no further reduction with a threshold of 40 kPa.…”
Section: Effect Of Water Stress Treatment On Grain Yield and Yield Cosupporting
confidence: 53%
“…A stress of 40 kPa during FL-PM resulted in significantly lower grain weight than stresses of 10 and 20 kPa at the same stage, and than all stresses at the other two stages. Castillo et al (2006) also found lower grain weight when drought stress was applied during grain filling. However, in the present experiment, when 40 kPa was applied at all three stages, there was no effect on grain weight.…”
Section: Effect Of Water Stress Treatment On Grain Yield and Yield Comentioning
confidence: 83%
See 1 more Smart Citation
“…In rice, leaf expansion stops completely when the root‐zone soil water pressure potential exceeds 50 kPa (Wopereis et al, 1996; Tuong and Bouman, 2003). Water stress may result in delayed flowering, reduce biomass production as a result of reduced transpiration, increase panicle sterility, lower the harvest index (HI), and ultimately impact grain yield (GY) (Xue et al, 2008; Castillo et al, 2006; Xiaoguang et al, 2005). Lafitte and Courtois (2002) observed a large genotype × water interaction for yields of upland rice.…”
mentioning
confidence: 99%